Upaya Meningkatkan Hasil Belajar Bahasa Inggris Materi Narratif Text melalui Model Pembelajaran Problem Based Learning Siswa Kelas VIII.A SMP Negeri 6 Mataram - Karyani, Susila (YASIN, 2023)
The objectives of this study were: 1) To find out that the PBL learning model can improve English learning outcomes Narrative Text Material for class VIII.A SMP Negeri 6 Mataram in the academic year 2022/2023; 2) To find out the PBL learning model can improve English learning outcomes Narrative Text Material for class VIII.A SMP Negeri 6 Mataram for the 2022/2023 academic year. The subjects of this study were 39 class VIII.A students of SMP Negeri 6 Mataram, consisting of 22 female students and 17 male students. The stages of this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The results of the research show that the success of the Problem Based Learning (PBL) learning model can be seen in the pre-cycle conditions, students who complete learning are 27 students (69.23%) of 39 students, with an average score of 80.77. After the learning improvements were implemented in cycle I, the number of students who completed their studies became 30 students (76.92%) with an average score of 83.82. In cycle II, it is known that all 39 students (100%) have successfully completed their studies, with an average score of 90.44. Based on these results, it is said that learning English with the Problem Based Learning (PBL) learning model can improve the mastery of learning outcomes according to what is planned for class VIII.A students of SMP Negeri 6 Mataram.